Indonesia Satu Buat Semua, Semua Buat Satu dalam Relasi Pemikiran Nasionalisme Soekarno dan Tan Malaka - Nonobenany, Yakobus Nekin (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2023)
This paper discusses the thoughts of Sukarno and Tan Malaka in the context of Indonesian nationalism. They both had a strong spirit of nationalism in the struggle to free Indonesia from colonialism and achieve independence. Sukarno emphasized national unity, Indonesian leadership, and rejection of colonialism. Meanwhile, Tan Malaka saw social and economic injustice and championed nationalism as part of the class struggle. Despite their different ideological approaches, both Sukarno and Tan Malaka fought to achieve Indonesian independence by mobilizing the unity of the people and opposing colonialism. Their ideas helped shape Indonesia's national identity and consciousness. However, this paper also highlights the current Indonesian crisis, such as widespread corruption, social and economic inequality, a weak political system, identity conflicts, and religious fanaticism. Overcoming these crises requires political system reform and stronger law enforcement, increased social and economic equality, and dialogue between ethnic and religious groups. In this context, the nationalist ideas of Sukarno and Tan Malaka are still relevant. Indonesia should be an independent, just, equitable and sovereign country. Social justice for all Indonesians should be prioritized, and differences between regions and groups should be resolved to ensure equal justice. Excessive religious fanaticism should be overcome, and unity in diversity should be affirmed as the foundation of the Indonesian state. This paper provides insights into the nationalist thoughts of Sukarno and Tan Malaka and the challenges of the Indonesian crisis faced by the country today.AbstrakMakalah ini membahas pemikiran Sukarno dan Tan Malaka dalam konteks nasionalisme Indonesia. Keduanya memiliki semangat nasionalisme yang kuat dalam perjuangan membebaskan Indonesia dari kolonialisme dan meraih kemerdekaan. Sukarno menekankan persatuan nasional, kepemimpinan Indonesia, dan penolakan terhadap kolonialisme. Di sisi lain, Tan Malaka melihat ketidakadilan sosial dan ekonomi, dan mengadvokasi nasionalisme sebagai bagian dari perjuangan kelas. Meskipun memiliki pendekatan ideologis yang berbeda, baik Sukarno maupun Tan Malaka berjuang untuk mencapai kemerdekaan Indonesia dengan menggalang persatuan rakyat dan menentang kolonialisme. Ide-ide mereka membantu membentuk identitas dan kesadaran nasional Indonesia. Namun, makalah ini juga menyoroti krisis Indonesia saat ini, seperti korupsi yang meluas, ketidaksetaraan sosial dan ekonomi, sistem politik yang lemah, konflik identitas, dan fanatisme agama. Mengatasi krisis-krisis ini memerlukan reformasi sistem politik dan penegakan hukum yang lebih kuat, peningkatan kesetaraan sosial dan ekonomi, serta dialog antara kelompok etnis dan agama. Dalam konteks ini, ide-ide nasionalis Sukarno dan Tan Malaka masih relevan. Indonesia seharusnya menjadi negara yang merdeka, adil, setara, dan berdaulat. Keadilan sosial bagi semua warga Indonesia harus diprioritaskan, dan perbedaan antara wilayah dan kelompok harus diselesaikan untuk memastikan keadilan yang setara. Fanatisme agama yang berlebihan harus diatasi, dan persatuan dalam keberagaman harus diteguhkan sebagai landasan negara Indonesia.